The effects of sprint-assisted and sprint-resisted swimming on stroke mechanics - Maglischo, E. W.; Maglischo, C. W.; Zier, D. J.; Santos, T. R. (Journal of Swimming Research, 1985)
Four male and two female age-group swimmers were filmed sprinting butterfly. They swam approximately 40 feet under three conditions: 1) normally, 2) partially tethered by a swim belt, and 3) sprint-assisted using a tethered belt. Biomechanical and stroking factors were evaluated. 1.Sprint-resisted training caused shorter and slower stroking. 2.Sprint-assisted training increased stroke rate but only by shortening stroke length and not by changing hand velocity. 3.Stroke mechanics were changed in both forms of training, casting doubt on the efficacy of both forms of training. 4.This study could be considered an indictment of these training methods. Each encouraged swimmers to adopt less efficient mechanics. Implication: It was contended by the authors that the changes promoted by these training methods might not be transferred if they only constituted a small part of the training program. They also suggested that there might be other, but not yet recognized, values to these forms of training. It is recommended that these methods of training be treated cautiously and used sparingly. Their value might best be maximized early in basic training phases but could become counter-productive in more specific phases of training.